Canada's Ethics Commissioner and the Watchdog Model of Ethics Enforcement - Luc Juillet (Canadian Public Administration, 2026)
Abstract Despite notable progress, the OECD recently noted that conflict of interest regulation still suffers from poor implementation and how to ensure effective enforcement of ethics rules remains an important challenge. One popular but under‐examined approach is to rely on an ethics watchdog: an independent agency with few powers that can nevertheless investigate and publicly blame violators as a form of sanction and deterrence. To better ascertain the effectiveness of this model of ethics enforcement, we examine how Canada's Ethics Commissioner used investigations to enforce ethics rules over a fifteen‐year period, the media coverage that they have received, and the career consequences that adverse findings have had for the officials blamed by the Commissioner. We find that, while used to scrutinize even the most powerful officials, ethics investigations had little impact, casting doubt on the potential effectiveness of relying on publicity, shaming and reputational costs as tools of ethics enforcement.